Trabeculectomy with Healaflow versus Trabeculectomy for the Treatment of Glaucoma: A Case-Control Study - Dimitris Papaconstantinou; Andreas Diagourtas; Petros Petrou; Alexandros Rouvas; Athanasios Vergados; Chryssanthi Koutsandrea; Ilias Georgalas (Journal of Ophthalmology)
Purpose. To compare the outcomes of trabeculectomy with and without Healaflow (Anteis S.A, Geneva, Switzerland), a high molecular weight viscoelastic gel, in patients requiring glaucoma surgery. Methods. This was a retrospective, comparative, interventional case-control study. Forty patients formed two matched study groups and were analyzed (trabeculectomy alone (control) versus trabeculectomy with Healaflow (study)). Results. The postoperative levels of mean IOP were statistically significantly lower P<0.05 than preoperatively in both groups, for all time intervals. There was no statistical difference, at the end of the follow-up period, between the two groups in the mean values of the IOP (14.9 ± 3.2 mmHg for the study group versus 14.8 ± 3.3 mmHg for the control group). The number of antiglaucoma drugs used in the study group was reduced from a preoperative mean of 3.4 ± 0.75 to a 6-month postoperative mean of 0.6 ± 0.8 P<0.001 and in the control group from 3.6 ± 0.59 to 0.55 ± 0.9 P<0.001. Conclusions. Although trabeculectomy with Healaflow appears to be a safe procedure, we failed to identify any significant advantages in the use of Healaflow when compared with trabeculectomy alone, at the end of the 6-month follow-up period.